Smart Manufacturing for Sustainable Development & Its Future in India - Chatare, Rekha Dhananjay (International Journal of Computer Sciences and Engineering, 2022)
Manufacturing sector is continuously now and then blamed for heavy pollution and contamination. It is always associated with the environment deterioration. Whenever any industry setup its infrastructure, it is essential to get a green go from the environment conservation board. We know the real development of any country very much depends on the industrial development of the country. Manufacturing technologies are considered as the source for providing the goods and services for any further use and development. But it is also true that Environment protection carries the same importance as industrial development. That’s why it is mandatory to adopt those manufacturing technologies, which can promote the development without hampering the natural balance. Manufacturing technologies, which helps in sustaining the natural balance of environment come under the Smart manufacturing. Smart manufacturing is considered as the key for sustainable development. Smart manufacturing includes technologies like Artificial intelligence, Digital technologies, 3- Dimension printing, Block Technologies, Data Analytics, RFID and many more. This aim of this research paper is to identify the technologies which comes under Smart manufacturing and helps in Sustainable development. The researcher also wants to find the future scope of these technologies in India.